2020
DOI: 10.33448/rsd-v9i9.7379
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality and somatic cells of in natura milk produced in Alagoas State, Brazil

Abstract: Raw milk is a food with great consumption and economic value in Brazil. However, is susceptible of contamination by pathogenic bacteria. The aimed of this study was to evaluate the quality of in natura milk based on microbiological in three dairy farms, somatic cells counting (SCC), bacterial counting and his physical-chemical composition. Were made the following microbiological analysis: counting of mesophilic and psychrotrophic bacteria, coliforms at 30 ºC, coliforms at 45 ºC, Staphylococcus spp., Listeria s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Microbiological analysis revealed that the etiology of the subclinical mastitis of the two farms was due to two genera of microorganisms, Staphylococcus and Streptococcus. These agents are classified into infectious subclinical mastitis [3,12], where contamination occurs at the moment of milking, mainly by the hand of the milk and utensils. The result obtained shows that the most active agent of the pathology was Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiological analysis revealed that the etiology of the subclinical mastitis of the two farms was due to two genera of microorganisms, Staphylococcus and Streptococcus. These agents are classified into infectious subclinical mastitis [3,12], where contamination occurs at the moment of milking, mainly by the hand of the milk and utensils. The result obtained shows that the most active agent of the pathology was Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Subclinical mastitis can be diagnosed by the California Mastitis Test (CMT) and by laboratory tests that detect milk somatic cell count (SCC), milk from mast cells has high SCC, and a large industrial scale loss due to problems in the production of derivatives [2]. In addition, they can manifest in the function of failures in the animals' management [3] Post-dipping is one of the most effective measures of control of subclinical mastitis, which consists in the application of an antimicrobial agent, to disinfect and protect the ceilings, after milking, of the possible action of microorganisms from the external environment such as the microbiota of the animal's skin.…”
Section: Introductionmentioning
confidence: 99%